Radiation Treatment for Inoperable Local Relapse of Parathyroid Carcinoma With Symptomatic Hypercalcemia: A Case Report - Bollen, Heleen; Decallonne, Brigitte; Nuyts, Sandra (Frontiers in Oncology, 2021)
Background: Parathyroid carcinoma (PC) is an extremely rare malignancy, characterized by slow progression, frequent recurrences and difficult-to-control hypercalcemia which is typically the main contributor to the morbidity and mortality of these patients. Patients often undergo repeated surgical resections, whether or not in combination with adjuvant radiation treatment. The role of radiation therapy within the symptomatic treatment of PC currently remains unclear. Case description: We describe a 30-year-old male patient with an inoperable local relapse of PC and secondary symptomatic hypercalcemia, maximally pharmacologically treated. After a local radiation treatment to a total dose of 70 Gray in 35 fractions serum calcium and parathyroid hormone (PTH) levels decreased, accompanied by improvement of the severe gastro-intestinal disturbances. Conclusion: For patients with inoperable symptomatic PC despite maximal medical treatment who are in a good overall condition, radiation treatment can be considered in well-defined cases to decrease symptoms and improve quality of life.